Atypical preeclampsia-eclampsia syndrome at 18 weeks of gestation: A case report - Ugonna Aja-Okorie; Nnabuike Chibuoke Ngene (Elsevier, 2022)
Background: Preeclampsia is currently defined as new-onset hypertension occurring with significant proteinuria, maternal organ dysfunction, and/or placental insufficiency at or after 20 weeks of gestation. In the majority of cases, it occurs before 48 h postpartum. Therefore, preeclampsia occurring before 20 weeks of gestation or after 48 h postpartum is atypical and may not be easily diagnosed. Aim: A case of atypical preeclampsia is presented to highlight the need for increased vigilance by healthcare professionals to ensure timely diagnosis and treatment to prevent adverse outcomes. Case Presentation: A 29-year-old woman, gravida 3, para 1, with one previous miscarriage, commenced antenatal care at 10 weeks of gestation. Based on history and physical examination, the only risk factor for preeclampsia identified was a primipaternity. The patient had a single mid-trimester scan but no robust multimodal screening for preeclampsia using ultrasound or biomarkers. At 18 weeks of gestation, she presented to a primary healthcare clinic with headache, epigastric pain, and a documented single blood pressure reading of 169/71 mmHg. She was placed on alpha-methyldopa and managed as an outpatient. A day later, she had two episodes of seizures and was transferred to a tertiary hospital. She was diagnosed with atypical eclampsia and HELLP syndrome. Following MgSO4 therapy and stabilization, an uneventful termination of pregnancy was performed, and she recovered fully. Conclusion: Robust screening for preeclampsia using history and physical examination, ultrasonography, and biomarkers in the first trimester to identify women at high risk of the disease for prophylactic therapy with aspirin may prevent this disorder.